The Management of Medium Hazard Potential at Trimitra Sejati Jaya Ltd (Glue Production) - Maritha Nilam Kusuma; Safira Aulia Madinah (Journal of Civil Engineering, Planning and Design, 2022)
All industrial activities that use, store, produce, and transport hazardous chemicals in the workplace are required to control hazardous chemical to prevent occupational accidents and work-related diseases. Trimitra Sejati Jaya Ltd is a company engaged in the manufacturing industry that produces wood glue, paper glue, packaging, PVAc white glue, and hotmelt adhesive. In its working activities, Trimitra Sejati Jaya Ltd has a risks and hazards impact that requires medium hazard potential management. This research is a descriptive study that was conducted objectively to determine the control of medium hazard potential in Trimitra Sejati Jaya Ltd. The objective of this research is to find out the actual conditions in the field compared to the compatibility of the laws and regulations. Hazard identification, risk assessment and control at Trimitra Sejati Jaya Ltd were carried out using the HIRARC method. The level of risk dominating the work activities in this company was categorized as medium risk. Technical activities, design, construction, chemical material selection, as well as operation and maintenance of installations at Trimitra Sejati Jaya Ltd have been performed in accordance to the company regulations. Trimitra Sejati Jaya Ltd has several employees development activities, such as waste management and handling training and socialization, personal protective equipment usage socialization, fire fighting socialization, and internal briefings that have been carried out for several times. There are existed emergency response plan and procedures such as evacuation routes and assembly points signs, as well as provide fire extinguishers and first aid kits. There are no safe work procedure implemented at Trimitra Sejati Jaya Ltd yet, it only oriented on the existed Quality Management System